A duplex PCR assay for the simultaneous quantification of Bacteroides HF183 and crAssphage CPQ_056 marker genes in untreated sewage and stormwater. (May 2019) - Ahmed, Warish; Payyappat, Sudhi; Cassidy, Michele; Besley, Colin
Abstract: The HF183 marker gene, derived from the 16S rRNA gene of Bacteroides dorei, has been widely used to identify sewage pollution in environmental waters. CrAssphages are recently discovered DNA bacteriophages that are highly abundant in untreated sewage and have shown promises for tracking sewage contamination in environmental waters. In this paper, we report the development of a duplex quantitative PCR (qPCR) assay for simultaneous quantification of HF183 and crAssphage CPQ_056 marker genes in untreated sewage and sewage impacted stormwater. Same primer and probe sequences were used in the duplex qPCR assay as used in published simplex qPCR assays. The performance characteristics of the duplex qPCR assay were similar to its simplex counterparts. We validated the performance of the duplex assay in a collaborative laboratory study with the aim to evaluate reproducibility, sensitivity and concordance for field study. The concordance values between the simplex vs. duplex qPCR assays for HF183 and crAssphage CPQ_056 marker genes ranged from 96.7 to 100% and the mean concentrations of HF183 and CPQ_056 in environmental water samples were remarkably similar or in some cases slightly greater for the duplex qPCR assay suggesting the reliability of this assay for monitoring HF183 and CPQ_056 simultaneously. The newly developed duplex qPCR assay will be a valuable addition to the MST toolbox for sewage pollution monitoring and would allow rapid and comparative sample analysis. Highlights: Duplex qPCR assay can quantify HF183 and crAssphage CPQ_056 marker genes. Duplex and simplex qPCR assays showed 100% concordance for sewage samples. Duplex and simplex qPCR assays were highly correlated.